The role of a neurologist in deciding on the treatment options in epilepsy: therapy and/or surgery - K. V. Voronkova; A. I. Fedin; A. E. Nikitin; A. A. Zuev; N. V. Pedyash; D. M. Bochaeva (Эпилепсия и пароксизмальные состояния, 2019)
The existing approaches to treating epilepsy can be classified as therapeutic and/or surgical. In most cases, a patient with epilepsy is examined by a neurologist (or psychiatrist) and receives antiepileptic drugs (AEDs) in order to control seizures. And it is the neurologist who decides on referring the patient to the surgeon for further treatment if the medications have no effect. Undoubtedly, there are situations when, during the initial examination, the doctor reveals life-threatening lesions or brain abnormalities, which unequivocally indicate the necessity of surgical treatment. The present article addresses the issues of professional caution required from the neurologist in less-obvious clinical cases, when the doctor has to rely on his/her own clinical judgement in order to identify the “surgical” situations and refer the patient to a neurosurgeon for an adequate treatment.